STUDI DESKRIPTIF TERHADAP PENGGUNAAN BAHASA PADA REKLAME DI TOKO-TOKO FOTOKOPI SEKITAR KAMPUS STKIP PGRI SUMATERA BARAT PADANG - NIDDE PUSPITA (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
The problem in this research is the writing that was written Indonesian incompatiblewith standard Indonesian. Of the characteristics of the language used in the advertisementbillboards do not have to use a standard language so that researchers would like to describe theuse of language on the billboard of the standard and non-standard language. This study aimedto describe the use of standard and non-standard language on the billboard in photocopy shopsaround campus STKIP PGRI West Sumatra Padang seen from spelling and punctuation.This research is a qualitative descriptive method. The data in this study were takenfrom the advertisement in photocopy shops around campus STKIP PGRI West SumatraPadang. Object of study is the standard and non-standard language seen from spelling andpunctuation. Research instrument uses a camera to photograph the billboard at photocopyshops around campus STKIP PGRI West Sumatra Padang. The technique used to obtain thedata is done with the documentation that is taken with the photograph in the advertisementcopy shop then analyzed by (1) identifying the data, (2) classifying the data, (3) analyze, (4)draw conclusions.Results of data analysis can be see of 20 billboards language that found as many as222 consists of writing 193 words and punctuation as much as 29. Non-standard languagefound 278 consists of writing 238 words and punctuation as much as 40. It can be concludedthat the use of language in the advertisement copy in stores around campus STKIP PGRI WestSumatra Padang language used many using non-standard language. In accordance with thecharacteristics of billboards that billboards use interesting language, easy to understand, short,memorable and exciting. Standard language for comparison in the study.Key word : Descriptive, study, of Language, and in Advertising